2020
DOI: 10.1051/0004-6361/202038344
|View full text |Cite
|
Sign up to set email alerts
|

Search and analysis of giant radio galaxies with associated nuclei (SAGAN)

Abstract: We present the first results of a project called SAGAN, which is dedicated solely to the studies of relatively rare megaparsec-scale radio galaxies in the Universe, called giant radio galaxies (GRGs). We have identified 162 new GRGs primarily from the NRAO VLA Sky Survey with sizes ranging from ∼0.71 Mpc to ∼2.82 Mpc in the redshift range of ∼0.03−0.95, of which 23 are hosted by quasars (giant radio quasars). As part of the project SAGAN, we have created a database of all known GRGs, the GRG catalogue, from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 189 publications
8
80
1
Order By: Relevance
“…However, about 10 percent of GRGs have now been found to re-side in cluster environments. According to Dabhade et al (2020a), about 820 GRGs larger than 0.7 Mpc are known to date. However, owing to their large extent and low surface brightness, they are notoriously difficult to detect.…”
Section: Large and Giant Radio Galaxiesmentioning
confidence: 99%
“…However, about 10 percent of GRGs have now been found to re-side in cluster environments. According to Dabhade et al (2020a), about 820 GRGs larger than 0.7 Mpc are known to date. However, owing to their large extent and low surface brightness, they are notoriously difficult to detect.…”
Section: Large and Giant Radio Galaxiesmentioning
confidence: 99%
“…Mack et al 1998;Malarecki et al 2015). However, ∼10 per cent of GRGs have now been found to reside in cluster environments (Komberg & Pashchenko 2009;Dabhade et al 2020b;Tang et al 2020) and Lan & Prochaska (2020) recently found no difference between the environments of GRGs and that of galaxy control samples. Another…”
Section: Introductionmentioning
confidence: 97%
“…size 2 of 4.89 Mpc (Machalski et al 2008), though the majority of known GRGs are below 2 Mpc in extent (Dabhade et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations